Bridging Global Norms and Local Action: UN Women’s Transnational Advocacy Networks in Combating Gender-Based Violence in Indonesia - Dewi Fadhilatunnisa; Wawan Budi Darmawan; Anggia Utami Dewi (Yayasan Ilomata, 2026)
This research examines the role of UN Women’s Transnational Advocacy Networks (TANs) in addressing gender-based violence (GBV) in Indonesia during the 2020–2024 period, focusing on the 16 Days of Activism Against Gender-Based Violence campaign. GBV remains a persistent concern within Indonesia’s policy landscape, and transnational advocacy has become increasingly influential in shaping national discourses. Drawing on the Transnational Advocacy Networks framework developed by Keck and Sikkink, this research analyzes advocacy strategies operating through information politics, symbolic politics, leverage politics, and accountability politics. By concentrating on a defined temporal scope and a single advocacy initiative, the study provides an empirically grounded examination of UN Women’s advocacy practices in Indonesia. The research employs a qualitative methodology based on document analysis of UN Women publications, campaign materials, legal instruments, and reports produced by national institutions and civil society organizations. The findings indicate that advocacy activities predominantly operate through information and symbolic politics by producing and disseminating gender-related data and aligning campaign narratives with international gender equality norms. Overall, this research demonstrates that UN Women’s transnational advocacy in Indonesia primarily contributes to norm diffusion and policy agenda-setting, while post-legislative accountability remains limited across institutional contexts and enforcement practices at national and local levels contexts.